Volume 9: Offshore Geotechnics; Torgeir Moan Honoring Symposium 2017
DOI: 10.1115/omae2017-62714
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Floating Bridge Projects in Norway

Abstract: This paper describe the development of floating bridge projects along the coast of Norway. Over the decades, the need to replace existing ferry connections with fixed linkes has beed rapidly increasing. However, the Norwegian nature with its deep and wide fjords, together with low traffic numbers have given the engineers big challenges in designing cost effective bridges for many of the crossings. One solution that was developed in the late 80s and early 90s by a combination of offshore technology and bridge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Multiple caissons arise in many offshore projects, such as floating bridges [43] and mobile offshore bases [1]. In this section, the case of two caissons (Fig.…”
Section: Model Validationmentioning
confidence: 99%
“…Multiple caissons arise in many offshore projects, such as floating bridges [43] and mobile offshore bases [1]. In this section, the case of two caissons (Fig.…”
Section: Model Validationmentioning
confidence: 99%
“…Vertical cylinders with elliptical cross sections can be adopted as the foundations of some coastal/offshore bridges as well (Wan et al, 2017). A more common shape of the bridge's foundation, however, might be a quasi-elliptical section (Liu et al, 2017;Eidem 2017). For all these marine structures, the radiation problem of a cylinder with different cross-sections is involved in either their operation or installation.…”
Section: Introductionmentioning
confidence: 99%
“…"rectangular" or "quasi-elliptical". Recently, Liu et al (2016;2017) solved the wave diffraction problem of a uniform (i.e. bottom mounted) and a truncated cylinder with non-circular/elliptical cross section, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site considered in this study is the Bjørnafjorden located on the west coast of Norway, as shown in Fig. 1 Several floating bridge concepts have been proposed for the crossing of Bjørnafjorden, including submerged floating tube bridge concept, cable stayed bridge with towers supported by TLP (tension leg platform) concept, sideanchored straight pontoon supported floating bridge concept, and end-anchored curved pontoon supported floating bridge concept [2]. Among them the endanchored curved floating bridge concept is considered in this study, as shown in Figs.…”
Section: Introductionmentioning
confidence: 99%